Beyond Phosphate Binding: A Systematic Review and Meta-Analysis on the Efficacy and Safety of the Novel Paracellular Phosphate Inhibitor, Tenapanor, for Hyperphosphatemia in Dialysis Patients - Eva Julita; Ian Effendi; Zulkhair Ali; Novadian; Suprapti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Hyperphosphatemia is a critical driver of cardiovascular morbidity and mortality in patients with chronic kidney disease (CKD) undergoing dialysis. Current management, reliant on phosphate binders, is hampered by high pill burden and poor adherence. Tenapanor, a first-in-class, minimally-absorbed sodium/hydrogen exchanger 3 (NHE3) inhibitor, reduces paracellular phosphate absorption. We performed a systematic review and meta-analysis of all available Phase 3 trials to quantify its efficacy and safety. Methods: We searched PubMed, Embase, and Cochrane CENTRAL through October 2025 for Phase 3 clinical trials evaluating tenapanor for hyperphosphatemia in dialysis patients. Data were extracted from 6 eligible studies (N=1573). We conducted separate random-effects meta-analyses for different study designs: 1) parallel-group monotherapy vs. placebo, 2) withdrawal-design monotherapy vs. placebo, 3) parallel-group add-on therapy vs. placebo, and 4) safety (diarrhea incidence) vs. placebo. Efficacy was measured by Mean Difference (MD) in serum phosphate change; safety by Risk Ratio (RR). Results: Tenapanor demonstrated significant efficacy across all study designs. In parallel-group monotherapy (1 study, N=167), tenapanor was superior to placebo (MD: -1.89 mg/dL; 95% CI: -2.36 to -1.42). In withdrawal-design studies (2 RCTs, N=373), tenapanor maintained serum phosphate levels significantly better than placebo (Pooled MD: -0.75 mg/dL; 95% CI: -1.05 to -0.45; I2=0%). As an add-on therapy (1 RCT, N=235), tenapanor provided additional phosphate reduction versus binders alone (MD: -0.65 mg/dL; 95% CI: -0.96 to -0.35). Tenapanor significantly increased the risk of diarrhea versus placebo (3 RCTs, N=521; Pooled RR: 4.10; 95% CI: 2.50 to 6.72; I2=30%), which was the primary adverse event leading to discontinuation. Conclusion: Tenapanor represents a new mechanistic paradigm for hyperphosphatemia management. It is a highly effective phosphate-lowering agent, both as monotherapy and add-on therapy, but is associated with a significant, mechanism-based risk of gastrointestinal side effects.